Anonymous
Anonymous asked in Science & MathematicsMathematics · 5 months ago

Solve the following differential equation:?

dx=(y/(1−x^2y^2))dx+(x/(1−x^2y^2dy))

.................. = constant

2 Answers

Relevance
  • JOHN
    Lv 7
    5 months ago
    Favorite Answer

    Answer

    Attachment image
    • Log in to reply to the answers
  • Vaman
    Lv 7
    5 months ago

    dx=(y/(1−x^2y^2))dx+(x/(1−x^2y^2dy)) .................. = constant

    I think, this should be df=0= (y/(1−x^2y^2))dx+(x/(1−x^2y^2dy))

    • Log in to reply to the answers
Still have questions? Get answers by asking now.